ANALISIS SEMIOTIKA REPRESENTASI KECURANGAN PEMILU DALAM FILM DOKUMENTER DIRTY VOTE - Dimas Erdhinta Pratama Putra; Fatma Retha Hazmy (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2024)
This research uses a descriptive study with a qualitative approach. Data was obtained by watching the film repeatedly and selecting scenes that represent the forms of election fraud design 2024. The theory used for analysis is Julia Kristeva's semiotic theory. Although Julia Kristeva's semiotic theory focuses on poetic language, the researcher tries to apply the theory to film media to explore the representation of election fraud. The results show that the representation of electoral fraud is shown through the genotext meaning of the film while the visuals shown to the audience are the phenotext. while the concept of abjection helps explain the audience's emotional reaction to the images depicting electoral fraud. The film's intertextuality connects it to the wider socio-political context, showing how fraud and power undermine the integrity of the democratic process. In conclusion, "Dirty Vote" succeeds in raising awareness and critical reflection on the importance of integrity in politics and elections.